2020
DOI: 10.1111/joor.13068
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin combined with ice stimulation improves swallowing function in patients with dysphagia after stroke: A randomised controlled trial

Abstract: Background Dysphagia is a common condition after stroke, and it is associated with many complications. Early and effective treatments are essential to the prognosis of patients with dysphagia. We aimed to evaluate the effects and safety of capsaicin combined with ice stimulation in patients with dysphagia after stroke. Methods Patients with dysphagia admitted to our hospital from December 2017 to December 2019 were included. The control group received the ice stimulation, and the experimental group received th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 39 publications
0
32
0
1
Order By: Relevance
“…First and most importantly is ice stimulation, which is an effective method to improve the motor and sensory activities of the tongue and soft palate through repeated mechanical, temperature, and pressure stimulation [16]. It increases the sensitivity of the swallowing reflex areas by stimulating the sensory input nerve fibers and eventually induces the swallowing reflex to improve the swallowing function [17,18]. Kawakami,M et al first reported the excitability of the human cortical swallowing motor pathway after oral ice stimulation and found that oral ice stimulation increases the excitability of the corticobulbar projection to the mylohyoid muscles, but ice stimulation to the superficial neck skin does not have any effects [19].…”
Section: Discussionmentioning
confidence: 99%
“…First and most importantly is ice stimulation, which is an effective method to improve the motor and sensory activities of the tongue and soft palate through repeated mechanical, temperature, and pressure stimulation [16]. It increases the sensitivity of the swallowing reflex areas by stimulating the sensory input nerve fibers and eventually induces the swallowing reflex to improve the swallowing function [17,18]. Kawakami,M et al first reported the excitability of the human cortical swallowing motor pathway after oral ice stimulation and found that oral ice stimulation increases the excitability of the corticobulbar projection to the mylohyoid muscles, but ice stimulation to the superficial neck skin does not have any effects [19].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, there is a related body of literature, in which capsaicin in different modes of administration is suggested to improve cough and/or swallowing function. This literature includes studies of capsaicin ointment which is applied to the external auditory canal, under the hypothesis that this could stimulate the auricular branch of the vagus nerve (Arnold’s nerve) and improve glottal closure and reflex cough via Arnold’s ear–cough reflex [ 49 ]; and studies in which capsaicin is added to ingested drinks or food [ 50 , 51 ] or administered to the oropharynx using a troche [ 52 ] or a frozen/cold swab containing capsaicin [ 53 , 54 ]. The latter studies are mainly based on the reasoning that capsaicin improves swallowing function by stimulating and enhancing oropharyngeal and laryngeal sensation [ 51 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ebihara (2006) has used black pepper oil for olfactory stimulation in older adults with dysphagia to improve their reflexive swallowing movements. Recently, Cui et al (2020) found that the use of capsaicin combined with ice stimulation can promote recovery of swallowing function in stroke patients. Therefore, capsaicin nebulization may…”
Section: Discussionmentioning
confidence: 99%